2012
DOI: 10.3382/ps.2011-01711
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive transport of folic acid in the intestine of laying hens with increased supplementation of dietary folic acid

Abstract: Different aspects of folic acid (FA) transport in the intestine of the laying hen have been characterized. Less is known about the adaptive response of this process to a dietary challenge. To this end, a study was conducted to evaluate the effect of increased dietary FA supplementation on the rate of intestinal FA transport and the expression of the intestinal folate transporter genes, the proton-coupled folate transporters (PCFT) and the reduced folate carrier (RFC), in the laying hen. Twenty-four Shaver Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…These results are in agreement with the findings of Tactacan et al (2012), who found that the egg and plasma folate concentrations of birds fed 10 or 100 mg of FAsupplemented diets significantly increased compared with those of birds fed the control diet. A proportionate increase in both plasma folate and egg folate concentrations is an indication that circulating blood folate are transferred efficiently into the egg (Sherwood et al, 1993;House et al, 2002;Hebert et al, 2005).…”
Section: Plasma Folic Acid and Egg Folate Contentsupporting
confidence: 93%
“…These results are in agreement with the findings of Tactacan et al (2012), who found that the egg and plasma folate concentrations of birds fed 10 or 100 mg of FAsupplemented diets significantly increased compared with those of birds fed the control diet. A proportionate increase in both plasma folate and egg folate concentrations is an indication that circulating blood folate are transferred efficiently into the egg (Sherwood et al, 1993;House et al, 2002;Hebert et al, 2005).…”
Section: Plasma Folic Acid and Egg Folate Contentsupporting
confidence: 93%
“…intake would be needed to induce toxicity. Though there are limited studies on feeding high doses of FA to broiler chickens, recent studies with laying hens have demonstrated non-toxicity of high doses of FA (Tactacan et al 2012). A possible explanation for the reduced growth performance in chickens fed 10 ppm FA in the current study is the metabolic relationship between FA and methionine.…”
Section: Resultsmentioning
confidence: 63%
“…Some studies were identified in the literature search reporting deposition of folates in food of animal origin. The FEEDAP Panel noted that new data derived from publications by Tactacan et al (2012), Altic et al (2016) and Bagheri et al (2019), all concerning deposition in the eggs, give very similar values to those retained in the former EFSA assessment (EFSA FEEDAP Panel, 2012). The study by Czarnowska-Kujawska et al (2020) concerning the deposition of folates in livers of chickens, turkeys, pigs and beef collected in retail/butchers, shows high deposition values however, no information was provided in the publication whether the samples were obtained from animals fed with folic acid-supplemented diets.…”
Section: Safety For the Consumersmentioning
confidence: 99%
“…The FEEDAP Panel noted that new data derived from publications by Tactacan et al. (2012), Altic et al. (2016) and Bagheri et al.…”
Section: Assessmentmentioning
confidence: 99%